Restricción financiera y crecimiento económico en México - Heri Oscar Landa Díaz (Investigación Económica, 2019)
– The aim of this paper is to examine the impact of financial development on economic growth. The contribution of both capital and credit market movements on the dynamics of Mexico's gross domestic product (GDP) over the period 1996-2017 is empirically tested using an Autoregressive Distributive Lag model. The main findings show that the deepening of the financial system generates bivalent effects on the evolution of GDP. The evidence also suggests an inverse relationship with bank intermediation and a positive one with stock market capitalization.
Keywords: C32; O47; G10; 330; Financial development; economic growth; Autoregressive Distributive Lag model